Step by step approach to English conversation - Sood, Madan (New Delhi : Goodwill Publishing House)
Step by Step Approach to English Conversation aims to facilitate its readers to approach and apprehend the rules of English Grammar in a step-by-step manner. It has been prepared bearing in mind the readership extent from almost all walks of life. Therefore, it is useful not only for the students of schools, colleges and those preparing for competitive examinations but also for those who want to communicate effectively for official, commercial, political or social purposes. The book ensures to coach the rules and regulations of English language such that readers are sure to overcome their lapses in the same.
Keywords: English Conversation